Bayt al-Māl wa al-Tamwīl and Community Economic Empowerment - Nurholis, Ahmad (Islamicate Institute, 2024)
This paper analyzes the role of Bayt al-Māl wa al-Tamwīl (BMT) as an Islamic microfinance institution in developing community economies. By integrating social and commercial functions, BMTs manage zakat and charitable funds while also providing financing through profit-sharing and qard al-ḥasan contracts. The research employs a qualitative literature review using books, journal articles, dissertations, and institutional publications. Findings reveal that BMTs enhance financial inclusion, empower micro and small enterprises, and strengthen community resilience. Challenges include limited governance capacity, technological constraints, and regulatory inconsistencies. Nevertheless, opportunities lie in digital transformation, government support, and alignment with Sustainable Development Goals. Theoretically, the study contributes to Islamic finance discourse by linking social and commercial finance in a hybrid institutional model. Practically, it offers strategies for policymakers and practitioners to strengthen BMT operations, expand outreach, and optimize their role in community economic development